Experimental study on vortex induced vibration (VIV) of a wide-D-section cylinder in a cross flow - Qingyang Wang; Mogeng Li; Shengjin Xu (Theoretical and Applied Mechanics Letters, 2015)
Wake structures and vortex induced vibration (VIV) of a spring-supported wide-D-section cylinder were experimentally investigated using an X-wire, a novel phase-locked particle image velocimetry (PIV), and an acceleration sensor at a low speed wind tunnel. Compared with the fixed case, the 2P (two pair) vortex mode as defined by Govardhan and Williamson (2000) rather than S (single vortex) mode exists in the wake. The velocity deficit behind the cylinder is much larger than that of fixed case. The mean drag coefficient increases from 1.42 for the fixed case to 1.64 for the vibrating case. The Reynolds stress presents even distribution and small with increased distance of X/D=−2 to X/D=−10. The power spectra density based on accelerator and hot wire data presents a highlight identical. It shows that after a strong interaction the cylinder vibration and the vortex shedding come to a stable state. The vortex shedding is totally locked on and controlled by the cylinder vibration.